2006
DOI: 10.1017/s0952523806233558
|View full text |Cite
|
Sign up to set email alerts
|

Color naming and categorization in inherited color vision deficiencies

Abstract: Dichromatic subjects can name colors accurately, even though they cannot discriminate among red-green hues (Jameson & Hurvich, 1978). This result is attributed to a normative language system that dichromatic observers developed by learning subtle visual cues to compensate for their impoverished color system. The present study used multidimensional scaling techniques to compare color categorization spaces of color-vision deficient (CVD) subjects to those of normal trichromat (NT) subjects, and consensus analysi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(20 citation statements)
references
References 13 publications
2
18
0
Order By: Relevance
“…Another study indicated that dichromats’ performance was significantly better (i.e. more similar to normal observers’ performance) in a color-naming task using eight basic color terms (BCT: red, green, yellow, blue, brown, pink, orange, and purple) consisting of naming color samples than it was in a free sorting task [5]. Recently, Lillo et al [7] reported that when the participants’ task was to select the best example of a given BCT, there was a significant difference between dichromats and NTs only for derived colors (brown, purple, orange, pink and gray) but not for primary colors (red, green, yellow, blue, black and white).…”
Section: Introductionmentioning
confidence: 97%
“…Another study indicated that dichromats’ performance was significantly better (i.e. more similar to normal observers’ performance) in a color-naming task using eight basic color terms (BCT: red, green, yellow, blue, brown, pink, orange, and purple) consisting of naming color samples than it was in a free sorting task [5]. Recently, Lillo et al [7] reported that when the participants’ task was to select the best example of a given BCT, there was a significant difference between dichromats and NTs only for derived colors (brown, purple, orange, pink and gray) but not for primary colors (red, green, yellow, blue, black and white).…”
Section: Introductionmentioning
confidence: 97%
“…It is well established that dichromats often identify colors correctly (some of the time) that are on the same dichromatic line of confusion and that their use of color names does not correspond to their color discrimination ability. [13][14][15][16][17][18][19][20][21] Their use of color names depends on experience, 14,21 size of the stimuli, 15,17,20 both relative and absolute brightness differences in the stimuli, 13,14,16,18,21 and whether there are constraints placed on the color names. 14,19,20 Some of these factors are likely responsible for the error asymmetries in our results.…”
Section: Discussionmentioning
confidence: 99%
“…14,17,19,21 Exactly how they use this information appears to be dependent on the display characteristics, context, and past experience. These higher order factors mean that modeling color discrimination and identification data within linear and nonlinear color vision models will be unsatisfactory.…”
Section: Discussionmentioning
confidence: 99%
“…One deuteranope, in particular, behaved exactly like someone with normal color vision. Bonnardel (2006) required subjects to name 140 colored chips, presented individually against a grey background in random order using eight basic color terms.…”
Section: Color Languagementioning
confidence: 99%